The implications of COVID-19 for student equity in Australian higher education. Issue 6 (2nd November 2021) - O'Shea, Sarah; Koshy, Paul; Drane, Catherine
ABSTRACT: The COVID-19 pandemic has both widened and exacerbated student equity issues in Australian higher education, just as it has increased economic and social disadvantage in the general population. This article identifies the immediate impacts of the pandemic on existing equity structures, mapping potential areas for research analysis and policy responses. Given the pervasive nature of COVID-19, it is proposed that a whole-of-system approach be used, and in addition to focusing on existing student equity categorisations, a holistic approach to understanding disadvantage over the university student life cycle is undertaken to ensure the response to this health crisis is both targeted and timely. The article identifies emerging repercussions of the pandemic that will drive long-term structural changes in Australian higher education, as well as the community and labour market. Based on these observations, the key challenges facing the student equity sector are identified and possible responses provided.